OVERVIEW OF PHBS IMPLEMENTATION IN STUDENTS AT SD PRIVATE PUTERI SION SIMPANG SELAYANG MEDAN TUNTUNGAN DISTRICT YEAR 2022 - Vina Y.S. Sgalingging; Amnita Ginting; Aperida Giawa (Sean Institute, 2023)
Competition in the business world, especially in the increasingly difficult printing world, requires developers to find strategies to increase orders for printed pr. Clean and healthy living behavior is a behavior that must be practiced by each individual with his own awareness to improve his health and play an active role in realizing a healthy environment. PHBS must be applied in every content of human life anytime and anywhere.Purpose: This study aims to determine the overview of PHBS implementation for students at Putri Sion Simpang Selayang Private Elementary School, Medan Tuntungan District in 2022. The technique used in this study was total sampling. Total sampling is a sampling technique, where the number of samples is equal to the total population of 70 respondents.Results: Based on the results of a study with a sample of 70 respondents regarding the description of the implementation of clean and healthy living behavior at SD Puteri Sion Simpang Hose, Medan Tuntungan District in 2022, it can be concluded: That the implementation of PHBS in the good category was obtained by 39 respondents (55%), and the sufficient category was obtained by 31 respondents (45%). Private Elementary School students are expected to realize the importance of PHBS in the school environment and become role models for other students and actively carry out PHBS activities.